Assume that $(G,*)$ and $(H,o)$ are groups and that $f:(G,*) \rightarrow (H,o)$ is a homomorphism.

Let $e_G$ and $e_H$ denote the identity elements of $G$ and $H$, respectively. Show that $f(e_G)=e_H$.

Approach: $f(e_G)=f(a*a^{-1})$ for $a,a^{-1} \in G$, so $f(a*a^{-1})=f(a)of(a^{-1})$.

If that’s true, then how do we know that $f(a^{-1})$ is the inverse of $f(a)$?

  • 1
    $\begingroup$ You don't, that would require $f(e)=e$. But try your same argument but with $a=e$ and it will work, we know $e^{-1}=e$ right. $\endgroup$ Aug 1, 2016 at 4:13
  • $\begingroup$ I think you can carry on with $f(a)f(a^{-1}) = f(a)f(a)^{-1} = e_H$. If you are allowed to use $f(a^{-1}) = f(a)^{-1}$ $\endgroup$
    – IAmNoOne
    Aug 1, 2016 at 4:26
  • 1
    $\begingroup$ @Nameless, that's what I have to prove next $\endgroup$ Aug 1, 2016 at 4:26
  • $\begingroup$ @TheMathNoob, well I guess you can't use what I suggested. You need help with that one or...? $\endgroup$
    – IAmNoOne
    Aug 1, 2016 at 4:27
  • 1
    $\begingroup$ @TheMathNoob, well actually we can more or less use what did here. Since you know $f(a)f(a^{-1}) = e_H$, what must $f(a^{-1})$ be? Actually I think my initial comment was backwards. $\endgroup$
    – IAmNoOne
    Aug 1, 2016 at 4:30

3 Answers 3


Using the fact that $e_G\ast e_G=e_G$ yields $$ f(e_G)=f(e_G\ast e_G)=f(e_G)\circ f(e_G)$$

Now multiply both sides by the inverse of $f(e_G)$ to obtain $f(e_G)=e_H$.

  • $\begingroup$ ok so $f(e_G)=f(e_G) \circ f(e_G)$, $f(e_G) \circ f^{-1}(e_G)=(f(e_G)\circ f(e_G)) \circ f^{-1}(e_G)$ and hence $\circ $ is associative we can say $f(e_G)=e_H$ $\endgroup$ Aug 1, 2016 at 4:22
  • $\begingroup$ That's correct. $\endgroup$ Aug 1, 2016 at 4:23
  • $\begingroup$ That trick seemed to be very useless XD. $\endgroup$ Aug 1, 2016 at 4:24

The answers provided here are excellent, but here is something to just widen your mind for diversity.

So if $a\in G$ $$f(a) = f(a* e_G) = f(a)\circ f(e_G).$$

Left cancel by $f(a)^{-1}$ to get $e_H$

  • $\begingroup$ Oh woahhh XDDDDD $\endgroup$ Aug 1, 2016 at 4:37

We have $e_G = e_G \ast e_G$, then

$$f(e_G) = f(e_g \ast e_G) = f(e_G)\circ f(e_G).$$

Now, $$e_H = [f(e_G)]^{-1}\circ f(e_G) = [f(e_G)]^{-1}\circ (f(e_G)f(e_G)) = f(e_G).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.